The European Community - Durbin, Chris (New York : Watts, 1994)
Examines, through text, illustrations, and photographs, how the geography of the European Community has influenced its social, economic, and political structure.
The physical region -- Farming and food -- A policy for agriculture -- The rise and fall of industry -- Transport and a single market -- Spreading the wealth -- Trade and aid -- Environment 2000 -- A continent at peace? -- Databank.
Includes index and glossary.
Booklist.
Library Talk.
6.5
5-8
Keywords: European Communities -- Juvenile literature; European Communities; European Union; Human geography; Human ecology; Europe -- Geography -- Juvenile literature; Europe -- Civilization; Europe -- Civilization